Hepatitis C virus promotes t‐helper (Th)17 responses through thymic stromal lymphopoietin production by infected hepatocytes12. Issue 4 (14th March 2013) - Lee, Hai‐Chon; Sung, Sung‐Sang J.; Krueger, Peter D.; Jo, Yoon‐Ah; Rosen, Hugo R.; Ziegler, Steven F.; Hahn, Young S.
Abstract Hepatitis C virus (HCV) is a major cause of liver cirrhosis and hepatocellular carcinoma. Here we report that infection of hepatic cells by HCV stimulates nuclear factor kappa B (NFκB)‐dependent production of thymic stromal lymphopoietin (TSLP). Hepatocyte‐derived TSLP in turn conditions dendritic cells (DCs) to drive T‐helper (Th)17 differentiation. The TSLP secreted by HCV‐infected hepatoma cells is capable of activating human monocyte‐derived DCs by up‐regulating the expression of CD40, CD86, CCL17, CCL22, and CCL20 which are activating markers of DCs. In addition, the production of key cytokines for Th17 differentiation, transforming growth factor beta (TGF‐β), interleukin (IL)‐6, and IL‐21, is enhanced by human monocytes upon coculture with HCV‐infected cells. Importantly, the blockade of TSLP using neutralizing antibody prevented the activation and maturation of DCs as well as the production of Th17 differentiation cytokines. DC conditioning by TSLP secreted from HCV‐infected cells activated naïve CD4+ T lymphocytes, resulting in Th17 differentiation. Furthermore, we can detect substantial levels of hepatocyte TSLP in fibrotic liver tissue from chronic HCV patients. Thus, blockade of TSLP released by HCV‐infected hepatocytes may suppress the induction/maintenance of hepatic Th17 responses and halt the progression of chronic liver disease to fibrosis and liver failure. Conclusion: Hepatocyte‐derived TSLP conditions DCs to drive Th17 differentiation. Treatment of TSLP neutralizing antibody in HCV‐infected hepatocyte/DC coculture abrogates DC conditioning and thereby inhibits Th17 differentiation. (HEPATOLOGY 2013)